Práticas de letramento no processo de ensino-aprendizagem em português língua estrangeira - Barros, Webert Cavalcanti (2011)
Throughout two years (2008-2009), at the Federal University of Paraíba (UFPB), I tried to lead students from other countries to learn Portuguese as a Foreign Language (PFL) in a situated and contextualized way. From this perspective, the reflection upon the social uses of textual genres has become crucial, since, as is well known, we use genres in order to act in society. The theoretical contributions of Bronckart (1985, 1996, 1999, 2006, 2008) served as a foundation in this action research, in order to bring the students to act communicatively, that is, through language. Therefore, my research questions are the following: do the literacy practices in PFL influence the way in which students position themselves when developing certain textual genres? What are the consequences or impacts of these practices in the way they position themselves in written texts? Do marks of enunciation, more precisely, the modalizations used by students, favor the achievement of the objectives in mind? My hypothesis revolved around the belief that during the development of written textual production, students use enunciative mechanisms, which, on guiding the reader´s interpretation, constitute key elements for achieving the goals which motivated the students to construct such texts. Dwelling on the analysis of two textual genres, namely, educational memories and letters (personal and addressed to public bodies), a comparison is made between texts written by students of different levels (basic/advanced), so as to find out whether the texts written by elementary level students highlight the development of these practices in a significant way, as well as between students from the same level (basic/basic, advanced/advanced), so as to comprehend if the relevance of these practices relate to an isolated case, or whether, in fact, they were reaching the majority of the students from the same level. The analyzed genres reveal that students generally knew how to deal with words, with good levels of persuasion, in view of the objectives, as well as with the interlocutor in mind. Although students, especially those from more advanced levels, already have well-developed literacy practices in their first language, the mere fact of having participated in a learning process that encompassed literacy practices enabled them to further develop certain skills in another language, in a new culture.